The Role of Green Entrepreneurial Motivation on Green Entrepreneurial Intention - Vina Islami; Siska, Elmira; Siti Mabrur Rachmah; Rio Sebastian, Dante (Pusat Riset dan Inovasi Nasional, 2025)
Green entrepreneurial education and motivation are critical because they foster a mentality oriented toward sustainability and environmental responsibility, which is necessary for creating green entrepreneurial purposes. This study examines the influence of green entrepreneurial education and green entrepreneurial motivation on green entrepreneurial intention among students at IPB University Business School. The study used a quantitative research design with a case study approach. Data collected by the questionnaire was distributed to 109 respondents using a simple random sampling technique. Data processing begins by conducting instrument quality tests, which include validity and reliability tests. Then the classic assumption test is run to ensure the model used does not have econometric problems. The t test and the F test are used to test the hypothesis. The findings show that partially, there is a positive and substantial impact of GEE on the formation of students' GEI (t calculated value 6.753 > t table 1.982). Partially, GEM has a positive and significant influence on GEI (t calculated 6.753 > t table 1.982). Simultaneously, GEE and GEM have a positive and substantial impact on GEI (F statistic is 1062.270, which is more than the F table 3.03). This study provides valuable insights for educational institutions to enhance support for students in developing green entrepreneurial intentions and initiatives.